Pengaruh Lingkungan Kerja Dan Pemberian Insentif Terhadap Kinerja Karyawan PT Digital Sumber Sejahtera Motor: The Impact of the Work Environment and Incentives on Employee Performance at PT Digital Sumber Sejahtera Motor - Calvin Dwi Pratama; Desy Suryani (CV Warnak Johanna Nusantara, 2025)
This research aims to analyze the influence of the work environment and provide incentives on employee performance at PT Digital Sumber Sejahtera Motor. A good work environment and an effective incentive system are expected to improve employee performance. The method used in this research is a survey with a questionnaire involving a sample of 35 respondents who are employees at PT Digital Sumber Sejahtera Motor. The independent variables in this research are the work environment and incentives, while the dependent variable is employee performance. The results of the analysis show that the work environment and providing incentives have a positive and significant influence on employee performance. The results of this research are (1) The work environment has a positive and significant influence on employee performance based on the results of the T test because the Sig value is 0.012 < 0.05 and the calculated t value is 2.656 > t table 2.036, so it can be concluded that Ho is rejected and Ha is accepted ( 2) Providing incentives has a positive and significant influence on employee performance based on the results of the T test because the Sig value is 0.000 < 0.05 and the calculated t value is 4.773 > 2.036, so it can be concluded that Ho is rejected and Ha is accepted, (3) the work environment and the provision of incentives together have a positive and significant influence on employee performance.